2021
DOI: 10.1088/1741-2552/abc29c
|View full text |Cite
|
Sign up to set email alerts
|

The temporal pattern of intracortical microstimulation pulses elicits distinct temporal and spatial recruitment of cortical neuropil and neurons

Abstract: Objective. The temporal spacing or distribution of stimulation pulses in therapeutic neurostimulation waveforms—referred to here as the Temporal Pattern (TP)—has emerged as an important parameter for tuning the response to deep-brain stimulation and intracortical microstimulation (ICMS). While it has long been assumed that modulating the TP of ICMS may be effective by altering the rate coding of the neural response, it is unclear how it alters the neural response at the network level. The present study is desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 109 publications
8
51
0
Order By: Relevance
“…In vivo voltage dye imaging in cat cortex found a progressive rise in excitation at the targeted region throughout a 10-Hz electrical stimulus train (300), supporting previous slice electrophysiology studies that had similarly concluded that high-frequency stimulation in cortical tissue preferentially activates excitatory neurons (301). Furthermore, a recent calcium imaging study in mice showed that excitatory neurons in L2/3 activate in response to specific stimulation frequencies, similar to visual cortical neurons tuned to a specific direction of drifting grating stimuli (296). Although our understanding of the biophysics underlying brain stimulation is evolving, many important questions remain to be explored.…”
Section: How Do Tms Es and Tdcs Work?supporting
confidence: 72%
See 1 more Smart Citation
“…In vivo voltage dye imaging in cat cortex found a progressive rise in excitation at the targeted region throughout a 10-Hz electrical stimulus train (300), supporting previous slice electrophysiology studies that had similarly concluded that high-frequency stimulation in cortical tissue preferentially activates excitatory neurons (301). Furthermore, a recent calcium imaging study in mice showed that excitatory neurons in L2/3 activate in response to specific stimulation frequencies, similar to visual cortical neurons tuned to a specific direction of drifting grating stimuli (296). Although our understanding of the biophysics underlying brain stimulation is evolving, many important questions remain to be explored.…”
Section: How Do Tms Es and Tdcs Work?supporting
confidence: 72%
“…In contrast, tDCS is less temporally and spatially specific than ES and TMS and acts by hyperpolarizing the resting membrane potential, making the anode region more excitable and the cathode less (292). Studies in human subjects and animal models both show that high-frequency stimulus trains excite the target more efficiently than low-frequency trains (293)(294)(295)(296)(297). Theta burst stimulation, a TMS protocol commonly used for cortical stimulation, uses three pulse bursts delivered at high frequency (for example, 50 Hz), repeated every 200 ms (5 Hz) (293).…”
Section: How Do Tms Es and Tdcs Work?mentioning
confidence: 99%
“…Additionally, we demonstrated that during 100 Hz-stimulation the activity of some neurons subsides during the pulse train after a short (1-2s) period of activation, whereas activation remains stable for others(28-30). This “onset” effect is thought to be mediated by inhibitory network recruitment in part because inhibitory neurons may entrain to 100 Hz-stimulation longer than excitatory neurons(28, 29). Therefore, investigating the temporal activation of cortical neurons during 100 Hz-stimulation with different waveforms could elucidate how the asymmetry of stimulation waveform modulates recruitment patterns(13, 23, 24, 29).…”
Section: Introductionmentioning
confidence: 99%
“…This “onset” effect is thought to be mediated by inhibitory network recruitment in part because inhibitory neurons may entrain to 100 Hz-stimulation longer than excitatory neurons(28, 29). Therefore, investigating the temporal activation of cortical neurons during 100 Hz-stimulation with different waveforms could elucidate how the asymmetry of stimulation waveform modulates recruitment patterns(13, 23, 24, 29).…”
Section: Introductionmentioning
confidence: 99%
“…Neural stimulator employed by Wagner et al (2018) produces stimulation trains with multiple discrete frequencies ( Figure 1D ) to enable locomotion in patients with a spinal cord injury. Brocker et al (2013) , Eles et al (2020) , and Soto-Breceda et al (2018) demonstrate delivery of a series of pulses with irregular inter-pulse-intervals to reduce synaptic fatigue in retina tissue or improve therapeutic effects in Parkinson’s treatments. Stimulators designed for these protocols require a dynamic control of timing of each individual pulse in the series ( Figure 1E ).…”
Section: Introductionmentioning
confidence: 99%